Advances in ceramic matrix composites - Low, It-Meng (Woodhead Publishing series in composites science and engineering., 2018)
Advances in Ceramic Matrix Composites, Second Edition, delivers an innovative approach to ceramic matrix composites, focusing on the latest advances and materials developments. As advanced ceramics and composite materials are increasingly utilized as components in batteries, fuel cells, sensors, high-temperature electronics, membranes and high-end biomedical devices, and in seals, valves, implants, and high-temperature and wear components, this book explores the substantial progress in new applications. Users will gain knowledge of the latest advances in CMCs, with an update on the role of ceramics in the fabrication of Solid Oxide Fuel Cells for energy generation, and on natural fiber-reinforced eco-friendly geopolymer and cement composites. The specialized information contained in this book will be highly valuable to researchers and graduate students in ceramic science, engineering and ceramic composites technology, and engineers and scientists in the aerospace, energy, building and construction, biomedical and automotive industries.